From Teacher Isolation to Teacher Collaboration: Theoretical Perspectives and Empirical Findings - Ostovar-Nameghi, Seyyed Ali; Sheikhahmadi, Mohsen (English Language Teaching, 2016)
This study aims at: (1) reviewing the underlying causes of teacher isolation; (2) unrevealing the negative effects of isolation on teachers' professional and personal life; (2) illustrating different modes of voluntary collaboration among teachers; (4) presenting substantive evidence is support of collaboration as an efficient mode of professional development, and (5) drawing implications for practice. Since collaboration leads to professional development and academic satisfaction, it is suggested that schools: (1) be structured in ways that maximize collaborative discussion among teachers; (2) create conditions that are conducive to growth and development for both teachers and learners; (3) reinforce study groups which aim at making teachers reflect on their current beliefs and practices and change them for the better; (4) move away from the once-popular teacher training courses towards teacher study groups, peer observation of teaching and mentoring, which are conducive to constructing knowledge rather than passively receiving knowledge. The review has many other clear implications for practitioners and other stakeholders.
Keywords: Communities of Practice; Efficiency; Evidence; Job Satisfaction; Mentors; Observation; Peer Teaching; Professional Development; Professional Isolation; Reflective Teaching; Teacher Collaboration; Teacher Improvement